Absence of predictable long-term molecular effect of ulipristal acetate (UPA) on the endometrium. Issue 5 (May 2019) - Kolanska, Kamila; Varinot, Justine; Canlorbe, Geoffroy; Bergeron, Christine; Mekinian, Arsène; Capmas, Perrine; Koskas, Martin; Daraï, Emile; Aractingi, Selim; Bendifallah, Sofiane; Chabbert-Buffet, Nathalie
Abstract: Research question: What are the effects of ulipristal acetate (UPA) on the expression of endometrial proliferation and maturation markers? Design: A total of 45 endometrium-containing blocks of hysterectomy samples from non-menopausal women with a diagnosis of moderate to severe symptoms of uterine fibroids: 14 women operated on at the end of a 3-month course of UPA; four women who had discontinued UPA treatment 1–12 months before surgery; 27 control unexposed samples (14 in the proliferative and 13 in the secretory phase). Immunohistochemical staining of Ki67, vascular endothelial growth factor-receptor 2 (VEGFR2), oestradiol receptor, progesterone receptor, interleukin-15 (IL-15), indoleamin-2, 3-dioxygenase (IDO) and C-C motif chemokine ligand-2 (CCL2) markers were analysed in both endometrial compartments and layers. Results: Under UPA, oestradiol receptor and progesterone receptor expression is similar to the proliferative phase in both layers, although with a decrease in cell proliferation. IL-15, IDO and CCL2 expressions are similar to the proliferative phase, suggesting a progesterone-antagonist effect of UPA. VEGFR2 staining suggests a trend to a mixed agonist–antagonist effect. No significant difference is observed in the post-UPA proliferative phase group compared with the control group in both layers of the endometrium. Conclusion: The effect of 3-month UPA treatment is mostly progesterone receptor antagonist-like. After treatment is discontinued, there are no signs of any long-term effects of this molecule on endometrial proliferation and maturation. Therefore, UPA may be administered to women willing to conceive in the short term without consequences for further implantation.